Cost-effectiveness of using sodium-glucose cotransporter type 2 inhibitors as a part of therapy for cardiovascular death prevention and achieving the Reduction of Cardiovascular Mortality indicator of the Healthcare Development state program in patients with chronic kidney disease and resistant hypertension - M. V. Zhuravleva; Yu. V. Gagarina; T. V. Marin (Российский кардиологический журнал)
Aim. To assess cost-effectiveness of using sodium-glucose cotransporter type 2 (SGLT2) inhibitors as a part of therapy for cardiovascular death prevention and achieving the Reduction of Cardiovascular Mortality indicator of the Healthcare Development state program in patients with chronic kidney disease (CKD) and resistant hypertension (RH).Material and methods. The target population is Russian comorbid patients with CKD and RH. The population size of 263303 people was determined based on Russian statistical data, literary sources and assumptions adopted in the study. To predict cardiovascular death, parametric modeling was used based on published clinical trial data. We calculated the drug costs required to prevent one cardiovascular death, as well as to achieve a target indicator for reducing cardiovascular mortality by one percent when using SGLT2 inhibitors in Russia as a whole and separately in each region.Results. The costs of CKD therapy in working-age patients with RH, who are indicated for therapy with SGLT2 inhibitors (n=263303) in 2025 were RUB 7,6 billion. The use of standard therapy with SGLT2 inhibitors in the target group of patients will prevent 2273 cardiovascular death cases in the first year, which will ensure the achievement of the Reduction of Cardiovascular Mortality indicator of the Healthcare Development state program by 9,9%.Conclusion. The ratio of additional costs to life years gained was RUB 2,49 million, which does not exceed 3 times the gross domestic product per capita (RUB 3,51 million) and indicates the economic feasibility of SGLT2 inhibitor therapy for CKD in patients with RH.